Expectations and challenges towards complying with the Occupational Safety and Health Act 1994: practice in KUKUM - Azuddin, Bahari, Lt Kol (B); Razi, Ahmad; Faridah, Wahab (Universiti Teknologi MARA (UiTM), 2008)
Organized by Universiti Teknologi MARA (UiTM), 8th - 9th August 2006 at Grand Season Hotel, Kuala Lumpur.